(untitled) (Global Journal of Science Frontier Research, 2022)
The global geo political system is determined The first elementary interpretation of the concept of freedom and its calculus is introduced Two global metahistorical goals of the realms of freedom and necessity have been identified The basic aspects of modeling history right and left in politics tradition innovation progress are determined The concept of an actor a player a decision-maker is formulated The formulation of the moral code of actors is given The inevitability of actors awareness of the choice between the realms of freedom and necessity is discussed which leads to a second deeper interpretation of the concept of freedom The space and time of actors are discussed and the relevant aspects of the transition between two target sets of actors are listed The content of ethics is determined providing a return to the realm of freedom and necessity Metaethics of the outcome of choice the third interpretation of the category of freedom